Alpha, beta and gamma Human Papillomaviruses in the anal canal of HIV-infected and uninfected men who have sex with men. Issue 1 (July 2015) - Donà, Maria Gabriella; Gheit, Tarik; Latini, Alessandra; Benevolo, Maria; Torres, Montserrat; Smelov, Vitaly; McKay-Chopin, Sandrine; Giglio, Amalia; Cristaudo, Antonio; Zaccarelli, Mauro; Tommasino, Massimo; Giuliani, Massimo
Summary Objectives Anal infection by cutaneous Human Papillomaviruses (HPV) has been rarely investigated. We aimed to assess the prevalence, genotype diversity, and determinants of mucosal (alpha) and cutaneous (beta and gamma) anal HPV infection in men who have sex with men (MSM). Methods Anal samples were collected with a Dacron swab. Alpha HPVs were detected using the Linear Array HPV genotyping test, while beta and gamma HPVs using a PCR combined with Luminex technology. Results A total of 609 MSM (437 HIV-uninfected and 172 HIV-infected, most of which were undergoing cART) were enrolled. Alpha, beta, and gamma HPVs were detected in 78.0%, 27.6% and 29.3% of the participants. Only alpha HPV prevalence was significantly higher among HIV-infected compared to uninfected MSM (93.0% vs. 72.1%, p < 0.0001). Beta2 and gamma10 represented the most frequent cutaneous HPV species, with no significant differences between HIV-infected and uninfected individuals. The most common alpha, beta, and gamma genotypes were HPV16, HPV111, HPV121, respectively. Alpha HPV infection was significantly associated with lifetime number of partners, receptive anal sex, and HIV status. Beta and/or gamma HPV infection showed no significant association with HIV status, socio-demographic or sexual behavioral factors. Conclusions A wide spectrum of mucosal and cutaneous HPV types is present in the anal canal. Only mucosal HPV prevalence increased significantly in cases of concomitant HIV infection.